Intoxicated driving and riding with impaired drivers: Comparing days with alcohol, marijuana, and simultaneous use. (1st August 2021) - Patrick, Megan E.; Graupensperger, Scott; Dworkin, Emily R.; Duckworth, Jennifer C.; Abdallah, Devon Alisa; Lee, Christine M.
Highlights: Of young adult simultaneous alcohol and marijuana (SAM) users, 2/3 rode with an impaired driver. 1/3 of young adult SAM users drove after use. More frequent SAM users rode with impaired drivers and drove after use more often. SAM use (compared to marijuana or alcohol only) on a given day was associated with riding with an impaired driver. SAM use (compared to marijuana only) on a given day was associated with driving after use. Abstract: Background: Young adults who engage in simultaneous alcohol and marijuana (SAM) use may be more likely to engage in unsafe behaviors including riding with impaired drivers and driving after alcohol and/or marijuana use. Methods: Young adult SAM users ( N = 408) self-reported their behavior for five 14-day bursts, yielding daily-level responses on a total of 14, 675 substance use days. Adjusted odds ratios (AOR) estimated the likelihood of riding with an impaired driver and of driving after use on SAM use days compared to alcohol- or marijuana-only use days. Results: More frequent SAM users were more likely to ride with an impaired driver and to drive after use than less frequent SAM users (between-persons). On SAM use days, there were greater odds of riding with an impaired driver, compared to alcohol-only days (AOR = 1.28) and marijuana-only days (AOR = 2.22), and of driving after use, compared to marijuana-only days (AOR = 1.25). Driving after use was more likely on days with non-simultaneous alcohol and marijuana use compared to SAM use (AOR = 1.59). Conclusions: Riding with an impaired driver is common among young adult substance users, and more likely following simultaneous use of alcohol and marijuana compared to other types of alcohol and marijuana use. Driving after use is more likely after SAM use than marijuana-only use days, but most likely on days when both alcohol and marijuana were used but not simultaneously. Future research on situation-level predictors of riding and driving-related risks among young adults is warranted.